Nuss Procedure for a Patient with Negative Haller Index - Mariela Dore; Paloma Triana Junco; Carlos De La Torre; Alejandra Vilanova-Sánchez; Monserrat Bret; Gaspar Gonzalez; Vanesa Nuñez Cerezo; Javier Jimenez Gomez; Jose Luis Encinas; Francisco Hernandez; Leopoldo Martínez Martínez; Manuel Lopez Santamaria (Georg Thieme Verlag KG, 2018)
Abstract Introduction Minimally invasive repair for pectus excavatum (MIRPE) is controversial in extremely severe cases of pectus excavatum (PE) and an open repair is usually favored. Our aim is to describe a case of a patient with an extremely severe PE that underwent a minimally invasive approach. Case report An 8-year-old girl with severe sternum depression was assessed. She had a history of exercise intolerance, nocturnal dyspnea, fatigue, and shortness of breath. Chest computed tomography showed that sternum depression was posterior to the anterior vertebral column; therefore, Haller and correction index could not be measured. Spirometry indicated an obstructive ventilation pattern (forced expiratory volume in 1 second = 74.4%), and echocardiogram revealed a dilated inferior vena cava, mitral valve prolapse with normal ventricular function. After multidisciplinary committee evaluation, a MIRPE approach was performed. All symptoms had disappeared at the 3-month postoperative follow-up; the desired sternum shape was achieved and normalization of cardiopulmonary function was observed. The Nuss bars were removed after a 2-year period. After 18-month follow-up, the patient can carry out normal exercise and is content with the cosmetic result. Conclusion Nuss procedure is feasible in our 8-year-old patient. In this case, both the Haller and correction index were not useful to assess the severity of PE. Therefore, under these circumstances, other radiologic parameters have to be taken into consideration for patient evaluation.